Pratarmė - Ramonienė, Meilutė (Kalbotyra, 2011)
This issue of Kalbotyra contains articles based on papers presented at the 2nd international conference of the Lithuanian Association of Applied Linguistics entitled “Languages and People: Dialogues and Contacts”. The conference was held on September 23-24, 2010 at Vilnius University to mark the 20th anniversary of the Department of Lithuanian Studies, Vilnius University. The papers covered a wide range of issues: language acquisition, learning and teaching, child language, sociolinguistics, text linguistics, discourse analysis, translation, linguistic landscapes, etc.We would like to express our deep appreciation to everyone who contributed to the success of the conference: plenary speakers Piet Van de Craen (Belgium), Elana Shohamy (Israel) and Jon White (United Kingdom); conference delegates and presenters; students and staff of the Faculty of Philology, Vilnius University; colleagues at the Institute of the Lithuanian Language; members of the Lithuanian Association of Applied Linguistics (LITAKA); conference sponsors – Research Council of Lithuania; conference partners – British Council, Lithuania and Goethe-Institut, Vilnius.